2019
DOI: 10.1177/1099800419872824
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Taste Differences Among People With Eating Disorders

Abstract: Background:Eating disorders are a significant cause of morbidity and mortality. The etiology and maintenance of eating-disorder symptoms are not well understood. Evidence suggests that there may be gustatory alterations in patients with eating disorders.Objective:This article systematically reviews research assessing gustatory differences in patients with anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED).Method:A systematic review was performed, following Preferred Reporting Items fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…The above sensitivity hypothesis does not apply to bitter-round matching. It has also been reported that patients with eating disorders showed lower sensitivity to bitter tastes compared to healthy individuals (for reviews, see Chao et al, 2019 andKinnaird et al, 2018). However, among our participants with greater tendencies toward eating disorders, the association between bitter taste and angular shape was stronger.…”
Section: Other Correlations Between Taste-shape Matching and Eating Dsupporting
confidence: 46%
See 2 more Smart Citations
“…The above sensitivity hypothesis does not apply to bitter-round matching. It has also been reported that patients with eating disorders showed lower sensitivity to bitter tastes compared to healthy individuals (for reviews, see Chao et al, 2019 andKinnaird et al, 2018). However, among our participants with greater tendencies toward eating disorders, the association between bitter taste and angular shape was stronger.…”
Section: Other Correlations Between Taste-shape Matching and Eating Dsupporting
confidence: 46%
“…They are unable to estimate their body size accurately, with a tendency toward overestimation (Gardner and Bokenkamp, 1996;Hamamoto et al, 2019;Mohr et al, 2010;Smeets et al, 1999). Furthermore, it has been demonstrated that taste perception in patients with eating disorders differs from that of healthy individuals (Chao et al, 2019;Dazzi et al, 2013;Kinnaird et al, 2018;Oberndorfer et al, 2013;Wagner et al, 2015). Several studies have focused on the perception of sweet taste because patients with eating disorders often avoid sweet foods.…”
Section: Perceptual Bias Related To Eating Disorder Tendenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 59 ] The specific course of therapy for EDs still needs to be accomplished, owing to the plethora of etiologic factors. [ 60 ] However, the associated complications like electrolyte imbalance with dehydration, hypotension, bradycardia, arrhythmias, and suicide tendencies may warrant urgent hospitalization. [ 61 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the hypothesis that female rats find the sweet taste more reinforcing and are therefore less sensitive to CTA at lower doses of LiCl. Cell-type analysis would benefit our understanding of how females differentially process sweet taste, a critical area of study in the field of eating disorders [108][109][110][111][112][113][114][115][116] . This result is particularly interesting considering their relative lack of USV expression in response to the rewarding stimulus.…”
Section: The C-fos Response During Cta Expressionmentioning
confidence: 99%